Preference for variety - Karen Kaiser; Rainer Schwabe (Banco de México, 2011)
We consider a decision maker who enjoys choosing from a varied set of alternatives. Building on behavioral evidence, we propose testable axioms which characterize preference for variety, and provide a representation theorem. We go on to illustrate the potential effects of preference for variety in a model of retailing. Consumer welfare may be decreasing in the competitiveness of the retailing sector as competition eliminates the scope for retailers to offer variety. Mainstream consumers with a preference for variety and consumers with eccentric tastes enjoy a symbiotic relationship. Competition over mainstream consumers makes retailers offer more exotic goods, while eccentric consumers subsidize their carrying costs.
Keywords: D0; D03; D4; 330; preferences; variety; representation theorem; retail; competition; Produktdifferenzierung; Einzelhandel; Konsumentenverhalten; Verhaltensökonomik; Theorie